Networking for sustainable cultural tourism activities and dynamics - Stević, Ivana (2013)
The present work examines the role and importance of networks in cultural tourism activities and dynamics, especially orientating the research to the case of UNESCO World Heritage Site of Oporto city, Portugal. For this purpose, comprehension of an extensive literature on the topic was necessary in order to create a set of hypothesis to base the research on. This literature included not only the concept of networks, but also of governance and public policy. Subsequently, the focus was put on the particular case of the mentioned World Heritage Site, which included content analysis of legal documentation, official manuals, reports, and strategic and management plans for the Site. The last step of the research was empirical research, which included interviews with representatives of the entities responsible for strategic decisions and the management of the Site. In order to make a synthesis between the theoretical and the practical part of the research, test the hypotheses and reach the necessary conclusions, qualitative methods were used, due to being considered most fitting for this case. The ultimate aim of this dissertation was to identify opportunities for a better management and preservation of cultural sites, and verify how networks can contribute to their sustainable development.